Interaction of Surface Crack on Solid Shaft due to Combined Loading - Awang, Muhamad Khairudin; Ismail, Al Emran; Ibrahim, Mohd Norihan; Ahmad Syahmi Azri (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Fracture is one of the main types of failure in solid cylinders, where the cracks exist when subjected to different types of mechanical loads. These cracks exist in the form of singular or multiple cracks. Multiple cracks can be one of the main reasons that further impacts the failure because the multiple cracks may have an interaction between one another. Therefore, this study is conducted to buckle down the problems that arise from the interactions of multiple cracks subjected to multiple loading. This study focuses on the interaction between multiple cracks located at the surface of the cylinder with parallel and non-coplanar parallel configuration. As the driving force for determining the crack interaction, the stress intensity factor (SIF) is selected. The Ansys finite element program is used to evaluate SIF’s different crack geometries and separation distances under various types of mechanical loads. The results show that the effect of crack interaction on parallel cracks and non-coplanar cracks are impacted by shielding and amplifying effect. The angle of inclination between the cracks demonstrates an important role in the interaction because it can change the actions of the interaction from shielding effect to amplifying effects and vice-versa.